(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
This experiment conducted at the Faculty of Science - Misurata University, inside a greenhouse in December -2016. This study was aim to comparing different concentrations of sludge from Misurata wastewater treatment, its effect on Allium cepa, and comparing it with chemical fertilizer NPK. Sludge was ground and added to the soil at different concentrations (15, 30, 45 tons / ha) in plastic ponds size (57 x 37 x 15 cm) at three repetitions for each treatment. The result showed that, the sewage sludge treatment was approximately to pH (6.86) and heavy metals in the allowed limits them compared to the German and Syria standard specifications for sludge in agriculture. Addition the results of the morphological study was unsignificant differences in all treatments compared to the control, although the physiological properties of sugars and proteins showed a significant increase to treatment (45 tons / ha), as well as in chlorophyll A when the two treatments (15 and 30 tons / ha). However, Mineral elements (potassium, calcium, magnesium, iron, chromium and cadmium) were unsignificant differences, while Copper, zinc, lead and arsenic were significant decreased compared to control, However all treatments were in the allowable limits compared to the German and Syrian standard specifications